The amino-terminal functions of the simian virus 40 large T antigen are required to overcome wild-type p53-mediated growth arrest of cells. - Quartin, R S (1994)
High levels of the p53 tumor suppressor protein can block progression through the cell cycle. A model system for the study of the mechanism of action of wild-type p53 is a cell line (T64-7B) derived from rat embryo fibroblasts transformed by activated ras and a temperature-sensitive murine p53 gene. At 37 to 39 degrees C, the murine p53 protein is in a mutant conformation and the cells actively divide, whereas at 32 degrees C, the protein has a wild-type conformation and the cells arrest in the G1 phase of the cell cycle. Wild-type simian virus 40 large T antigen and a variety of T-antigen mutants were assayed for the ability to bypass the cell cycle block effected by the wild-type p53 protein to induce colony formation at 32 degrees C. The results indicate that two functions within the amino terminus of T antigen are essential to induce cell growth: (i) the ability to bind to the retinoblastoma protein, Rb, and (ii) the presence of a domain in the first exon that appears to interact with the cellular protein, p300. Thus, the cell cycle arrest triggered by wild-type p53 may be overcome by formation of a T-antigen complex with Rb, p300, or both that could then function to either remove p53-mediated negative growth regulatory signals or promote a positive cell growth signal. Surprisingly, T antigen-p53 complexes are not required to overcome the temperature-sensitive p53 block to the cell cycle in these cells. These data suggest that simian virus 40 T antigen associated with Rb, p300, or both proteins can communicate in a cell with the functions of the wild-type p53 protein.